OPPORTUNITIES AND CHALLENGES OF DIGITAL SUPPLY CHAIN: A SYSTEMATIC LITERATURE REVIEW USING SCOR FRAMEWORK - Muhammad Saad Salahudin; Imam Baihaqi; Yen-Ching Liu (Transpublika Publisher, 2024)
Firms are increasingly integrating digital technology into their supply network systems for the purpose of attain global competitiveness. The utilization of digital technology has resulted in the Rise of a new supply chain management system known as the digital supply chain. Many parties believe that digital supply chain has several opportunities for companies, however, a number of researchers argues that the dependence on digital technology in the worldwide supply chain is accompanied by substantial obstacles. Therefore, this study intends to understand the opportunities and difficulties of digital supply chain and identify the future research agenda in this research area to develop better digital supply chain concepts and implementations. This research conducted systematic literature review through content analysis based on five dimensions in the SCOR model, which is plan, source, make, deliver, and return dimension. The analysis in this research finds that digital supply chain can enhances demand forecasting and product development in plan dimension, enables supplier selection and procurement automation in source dimension, facilitates smart and additive manufacturing in make dimension, optimizes inventory management, order management, transportation and logistics management in deliver dimension, as well as supports closed loop supply chain or circular economy in return dimension. However, the lack of infrastructure, policy, and coordination, along with financial, technical, and technological barrier, has become the common challenges of digital supply chain. Cybersecurity issue is also another main issue of the digital supply network. Through this analysis, the future research agenda can finally be taken in this research.